OPTIMALISASI WAKTU DAN BIAYA PROYEK RENOVASI RUMAH OLEH PT. XYZ DENGAN METODE CRASHING - Marcellio Kebayakenta Maha (2021)
Every project has a deadline, which means that the project must be completed before or right on the specified schedule. But in reality, in carrying out a project there are uncertain events that result in delays. This study uses a house renovation object that takes 87 days. This project experienced a delay of 8 days so that a project acceleration was needed, besides the objectives of this study were to identify critical activities, calculate the chances of project success, calculate time and cost after acceleration, and determine optimal time and cost after acceleration to overcome delays. The methods used are; CPM, PERT, and Crashing. By using the CPM method, 29 critical activities can be identified, then with the PERT method, the probability of project success is 82.89%, and through crashing the addition of 2 hours of overtime work can cut time to 77 days with a total cost of Rp. 265,980,986, while the addition of 3 hours of overtime can reduce the time to 74 days with a total cost of Rp. 274.111,080. The optimal alternative in this research is the addition of 2 hours of overtime work by accelerating 10 days with a total cost slope of Rp. 600,691.